FINDING LIST OF BLUE STARS IN HIGH GALACTIC LATITUDES - IRIARTE ERRO, B; CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1956)
We present a list of 817 blue stars found in the direction of the North Galactic Pole.
BOL OBS TONAN TACUB
Keywords: FINDING, LIST, BLUE STARS, HIGH, GALACTIC, LATITUDES; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS